2019
DOI: 10.1007/s10479-019-03269-0
|View full text |Cite
|
Sign up to set email alerts
|

Managerial efficiency and efficiency differentials in adult education: a conditional and bias-corrected efficiency analysis

Abstract: In efficiency studies, inputs and outputs are often noisy measures, especially when education data is used. This article complements the conditional efficiency model by correcting for bias within conditional draws, using the m out of n bootstrap procedure. With a unique panel dataset, we estimate managerial efficiency, which accounts for nondiscretionary variables, and explain efficiency differentials of adult education programs in Flanders. Our results suggest that the characteristics of learners in a program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
8
2
Order By: Relevance
“…More recently, Schiltz et al. (2020) extended the efficiency of primary, secondary, and higher education literature and explored the adult education programs in Flanders, Belgium. They applied a conditional efficiency model that corrects the noisy measures of inputs and outputs and found that learners’ characteristics matter for managerial efficiency and that the characteristics of the teacher and program explain efficiency differentials between adult education programs.…”
Section: Related Literaturementioning
confidence: 99%
“…More recently, Schiltz et al. (2020) extended the efficiency of primary, secondary, and higher education literature and explored the adult education programs in Flanders, Belgium. They applied a conditional efficiency model that corrects the noisy measures of inputs and outputs and found that learners’ characteristics matter for managerial efficiency and that the characteristics of the teacher and program explain efficiency differentials between adult education programs.…”
Section: Related Literaturementioning
confidence: 99%
“…As adult education attracts an increasing share of the total education budget, it is particularly interesting to analyse its productive efficiency. Contrary to significant attention of scholars to the efficiency of the compulsory education system (see an overview by De Witte and Lopez-Torres 2017), evidence on the performance of adult education is rare (an exception is Schiltz et al 2019).…”
Section: Extended Author Information Available On the Last Page Of The Articlementioning
confidence: 96%
“…Previous literature has primarily focused on the inefficiency of compulsory education (see De Witte and López-Torres (2017) for a review) and higher education (see Sneyers and De Witte (2017) for a review). To the best of our knowledge, only one paper has evaluated the inefficiency of adult education programs (Schiltz et al 2019). Using a conditional and bias-corrected Data Envelopment Analysis (DEA) model on Belgian data, Schiltz et al (2019) found that adult education programs could improve their efficiency by 4%, on average.…”
Section: Extended Author Information Available On the Last Page Of The Articlementioning
confidence: 99%
See 2 more Smart Citations